2013
DOI: 10.1155/2013/251398
|View full text |Cite
|
Sign up to set email alerts
|

The Antitumor Peptide CIGB-552 Increases COMMD1 and Inhibits Growth of Human Lung Cancer Cells

Abstract: We have demonstrated that the peptide L-2 designed from an alanine scanning of the Limulus-derived LALF32-51 region is a potential candidate for the anticancer therapy and its cell-penetrating capacity is an associated useful property. By the modification in the primary structure of L-2, a second-generation peptide (CIGB-552) was developed. However, the molecular mechanism underlying its cytotoxic activity remains partially unknown. In this study, it was shown that CIGB-552 increases the levels of COMMD1, a pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
79
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(84 citation statements)
references
References 36 publications
(34 reference statements)
5
79
0
Order By: Relevance
“…Treatment of H460 cells has a pro-apoptotic effect dependent on NF-κB signaling negative regulation and cell redox capacity impairment [5]. Correspondingly, here we detected using a bioinformatics-driven analysis the differential modulation of proteins associated to apoptosis and oxidative damage and to other processes such as metastasis and inflammation (See Table 3 in …”
Section: Bioinformatics-driven Analysismentioning
confidence: 66%
See 4 more Smart Citations
“…Treatment of H460 cells has a pro-apoptotic effect dependent on NF-κB signaling negative regulation and cell redox capacity impairment [5]. Correspondingly, here we detected using a bioinformatics-driven analysis the differential modulation of proteins associated to apoptosis and oxidative damage and to other processes such as metastasis and inflammation (See Table 3 in …”
Section: Bioinformatics-driven Analysismentioning
confidence: 66%
“…A suppressive subtractive hybridization (SSH) analysis on laryngeal tumor Hep2 cells showed that L-2 peptide treatment impacts the expression of genes that function in cancer related biological processes and pathways such as: DNA repair, mitosis, and angiogenesis [4]. Furthermore, a yeast two-hybrid study of CIGB-552 interactome identified COMMD1 protein as a target of CIGB-552 [5]. The importance of COMMD1 was later assessed by siRNA in H460 non-small cell lung cancer cells, with COMMD1 knockdown cells displaying a significant decrease in peptide cytotoxicity compared with control [5]; noticeably, peptide effect wasn't completely abrogated reflecting the occurrence of COMMD1-independent events.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 3 more Smart Citations